Affecting Factors Exclusive Breastfeeding Practices - Ajeng Galuh Wuryandari; Titik Hinriati (Alma Ata University Press, 2020)
The achievement of exclusive breastfeeding is still below the national target; this is a sign that the awareness of mothers in breastfeeding still needs to be improved. Based on the data of the Riskesdas year of 2018, the proportion of breastfeeding in infant ages 0-6 months in Indonesia are 37,3% and exclusive breastfeeding 9,3%. The government is targeting exclusive breastfeeding coverage of 80%. The coverage of exclusive breastfeeding in Jambi City is still below the government's target. Exclusive breastfeeding has a significant contribution to the development of optimally and endurance of children. This study aims to determine the factors that influence the practice of exclusive breastfeeding in Desa Suka Maju, Mestong District, Muaro Jambi Regency. This research is a quantitative analytic observational study with a cross-sectional approach. The sample in this study was all mothers who had babies totalling 112 mothers. Those who met the inclusion criteria were a purposive sampling technique. The data obtained were processed statistically using the chi-square test. The results showed that 30 people (26.8%) mothers gave exclusive breastfeeding, 15 people (18.81%) out of 80 mothers with low education provided exclusive breastfeeding and 15 out of 32 mothers with higher education provided exclusive breastfeeding. 11 people (15.5%) mothers with insufficient knowledge gave exclusive breastfeeding, and 19 people (46.7%) gave exclusive breastfeeding, but there were still 22 people (53,%) mothers with high knowledge who did not provide exclusive breastfeeding. And based on parity 22 people (32.4%) mothers with low risk gave exclusive breastfeeding, eight people (18.2%) mothers with high risk gave exclusive breastfeeding, and based on the results of statistical tests, education and knowledge had an effect on exclusive breastfeeding with a value P value <0.05 and maternal parity had no impact on exclusive breastfeeding with p value> 0.05. Education and knowledge affect exclusive breastfeeding, while parity does not guarantee that a mother is better at giving lactation. Researchers recommend that further research should use other variables such as knowledge and support from family members who are most influential in decision making and forms of husband support in the practice of exclusive breastfeeding.